2019
DOI: 10.1097/inf.0000000000002139
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Transmission in Danish Children: A Nationwide Register-based Study

Abstract: We found on-going TB transmission in Danish children within the households of a low TB incidence population. These findings emphasize the need for early diagnosis of TB in children, thorough contact tracing and increased focus on risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The occurrence of TB in young children is a well‐known marker of ongoing transmission of the infection in a society. National register studies of TB in children <15 years from Denmark and Switzerland reported median ages of five years . The results of the Danish study imply a gap in early detection of TB transmitted to small children.…”
Section: Discussionmentioning
confidence: 83%
“…The occurrence of TB in young children is a well‐known marker of ongoing transmission of the infection in a society. National register studies of TB in children <15 years from Denmark and Switzerland reported median ages of five years . The results of the Danish study imply a gap in early detection of TB transmitted to small children.…”
Section: Discussionmentioning
confidence: 83%